PENGARUH BRAND FAMILIARITY DAN PERCEIVED NOSTALGIA TERHADAP POST PURCHASE INTENTION DENGAN PERCEIVED VALUE SEBAGAI MODERATOR - Nathadiharja, Sri Sukartono; Tambun, Sihar; Ivada, Tia (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract- This research analyzes the influence of brand familiarity and perceived nostalgia on post-purchase intention, with perceived value as a moderating variable. Conducted on 146 respondents in Indonesia, it employs quantitative methods using the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach. The findings indicate that brand familiarity and perceived nostalgia significantly impact post-purchase intention, as consumers tend to make repeat purchases when they feel familiar with a brand or experience nostalgia. However, perceived value does not always strengthen this relationship. Among the five tested hypotheses, three were approved, while two were rejected. The study emphasizes the importance of marketing strategies that leverage nostalgia and brand familiarity to enhance loyalty. However, the moderating role of perceived value requires further examination in different contexts. This research contributes to consumer loyalty theory, particularly in markets influenced by emotional factors. A key contribution of this study is the integration of perceived nostalgia as a central factor in shaping post-purchase intention, an area not widely explored in previous literature. Additionally, it investigates the moderating role of perceived value in the relationship between brand familiarity and nostalgia on post-purchase intention, offering insights into the emotional dynamics of consumer loyalty. The novelty of this research lies in combining nostalgia and brand familiarity while examining perceived value’s moderating role in the Indonesian market, a relatively unexplored area. It also presents a PLS-SEM-based methodological approach to studying emotional factors in consumer behaviour. Keywords: Post-Purchase Intention; Perceived Nostalgia; Brand Familiarity; Perceived Value; Consumer Loyalty.